Define to be the term directly succeeding in A000027 . For example, because the term succeeding in the sequence is . Also define . is undefined everywhere else, and you may assume that is injective.
Define the operation as follows:
Define the operation as follows:
Determine the value of .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
In a nutshell: Ditch everything; just throw the two large numbers into a calculator and multiply them.
Complete solution:
Throughout this solution, consider natural numbers to include 0 (so they are 0 , 1 , 2 , 3 , … ).
Define ⊕ , ⊗ to be the operations defined here, and let + , × be the addition and multiplication we know. We can prove that ⊕ and ⊗ are the usual addition and multiplication defined for natural numbers.
Observe that S ( a ) is effectively equal to a + 1 , the natural number following a .
We induct on b to show that a ⊕ b = a + b . The base case b = 0 is done with the first axiom: a ⊕ 0 = a = a + 0 . Now assume the induction hypothesis: a ⊕ b = a + b . We then have:
a ⊕ ( b + 1 )
= a ⊕ S ( b ) by definition of S
= S ( a ⊕ b ) by second addition axiom
= ( a ⊕ b ) + 1 by definition of S
= ( a + b ) + 1 by induction hypothesis
= a + ( b + 1 ) by associative property of the usual addition
Thus we have proven the inductive step: from a ⊕ b = a + b follows a ⊕ ( b + 1 ) = a + ( b + 1 ) .
We then move to multiplication. Again, we use induction that a ⊗ b = a × b . The base case b = 0 is again done with the first axiom: a ⊗ 0 = 0 = a × 0 . Now assume the induction hypothesis: a ⊗ b = a × b . We then have:
a ⊗ ( b + 1 )
= a ⊗ S ( b ) by definition of S
= a ⊕ ( a ⊗ b ) by second multiplication axiom
= a + ( a ⊗ b ) by our result above
= a + ( a × b ) by induction hypothesis
= ( a × 1 ) + ( a × b ) by multiplicative identity
= a × ( 1 + b ) by distributive property of the usual multiplication over the usual addition
= a × ( b + 1 ) by commutative property of the usual addition
Thus we have proven the inductive step: from a ⊗ b = a × b follows a ⊗ ( b + 1 ) = a × ( b + 1 ) .
Thus we have established that the operations in the problem are none other than the usual addition and multiplication. Thus, throwing our numbers to a calculator, we obtain the result: 1 1 6 1 8 0 9 1 2 × 6 1 5 1 5 1 2 1 9 = 7 1 4 6 8 8 2 9 6 4 1 3 3 1 7 2 8 .
Afterword: Did you notice 1 , 1 6 , 1 8 , 0 9 , 1 2 and 6 , 1 5 , 1 5 , 1 2 , 1 9 spell APRIL FOOLS ? That is exactly what inspiring this problem. Make a seemingly convoluted problem which turns out to be none other what we are used to. One might be interested on reading more about Peano axioms .